A Bullet in the Supraspinatus Compartment Successfully Removed by Arthroscopy: Case Report and Review of the Literature - Alexandre Galland; Alexandre Lunebourg; Stéphane Airaudi; Renaud Gravier (Case Reports in Orthopedics)
Arthroscopic removal of bullet from intra-articular compartment has been described for several joints. Only few reports dealing with this condition in the shoulder have been reported especially for the glenohumeral and the subacromial compartments. We report the story of a fifty-seven-year-old man presenting a bullet in the supraspinatus compartment of his left shoulder successfully removed by arthroscopy.